Managing common eye problems in general practice. Issue 2 (February 2017) - Robinson, Ann
Abstract : Eye conditions are commonly encountered in primary care, but GPs often lack confidence with their diagnosis. This article gives an overview of some of the most common eye problems a GP might encounter and how they should be managed, including red flag symptoms to look out for when urgent referral is required.